Phenotypic switch of human and mouse macrophages and resultant effects on apoptosis resistance in hepatocytes - Bai, Li (Innate Immun, 2019)
Acute-on-chronic liver failure (ACLF) carries a significant burden on critical care services and health care resources. However, the exact pathogenesis of ACLF remains to be elucidated, and novel treatments are desperately required. In our previous work, we utilized mice subjected to acute insult in the context of hepatic fibrosis to simulate the development of ACLF and documented the favorable hepatoprotection conferred by M2-like macrophages in vivo and in vitro. In the present study, we focused on the phenotypic switch of human and mouse macrophages and assessed the effects of this switch on apoptosis resistance in hepatocytes. For this purpose, human and mouse macrophages were isolated and polarized into M0, M(IFN-γ), M(IFN-γ→IL-4), M(IL-4) or M(IL-4→IFN-γ) subsets. Conditioned media (CM) from these subsets were applied to human and mouse hepatocytes followed by apoptosis induction. Cell apoptosis was evaluated by immunostaining for cleaved caspase-3. As a result, M(IFN-γ) or M(IL-4) macrophages switched their phenotype into M(IFN-γ→IL-4) or M(IL-4→IFN-γ) through reprogramming with IL-4 or IFN-γ, respectively. Importantly, hepatocytes pre-treated with M(IFN-γ→IL-4) CMs exhibited much weaker expression of cleaved caspase-3, compared to those pre-treated with M(IFN-γ) CM, and vice versa. Together, phenotypic switch of macrophages toward M(IL-4) phenotype confers hepatocytes enhanced resistance to apoptosis.